The sociology of Katrina : perspectives on a modern catastrophe - Brunsma, David L.; Overfelt, David; Picou, J. Steven (Rowman & Littlefield Publishers, 2010)
The second edition of The Sociology of Katrina again brings together the nation's top sociological researchers in an effort to catalogue and deepen our understanding of the modern catastrophe of Hurricane Katrina. The new edition has been updated and revised throughout, including data about recovery efforts and conditions, and discussions of social issues like education, health care, crime, and the economy. This edition features a new chapter focused on the Katrina experience for people in the primary impact area, or ""gr.